1, 3, 5-Triazapentadienyltin(II) complexes and the additional reaction of phenylamine with N, N'-diisopropylcarbodiimide. (1st September 2018) - Guo, Zeling; Liu, Fang; Tong, Hongbo; Chao, Jianbin; Wang, Huan; Zhou, Meisu
Graphical abstract: A series of 1, 3, 5-triazapentadienyltin(II) complexes are reported. Their catalytic behaviors in additional reaction of phenylamine with N, N' -diisopropylcarbodiimide were discussed. Abstract: A series of tin(II) complexes 2 –5 bearing 1, 3, 5-triazapentadienyl ligands are reported: Sn[N(Ph)C(R′)NC(R′)N(SiMe3 )]2 [R′ = 1-piperidino, 2 ; NMe2, 3 ], [N(Ph)C(NMe2 )NC(NMe2 )N(H)]SnCl (4 ) and [N(SiMe3 )C(R′)NC(R′)N2 Sn2 ]2 (R′ = 1-piperidino) (5 ). Their single-crystal X-ray diffraction studies are presented. Compounds 3 and 4 are efficient catalysts for the catalytic addition of phenylamine to N, N' -diisopropylcarbodiimide giving guanidine.